Morphological Variability of Wild Cardoon (Cynara cardunculus L. var. sylvestris) Populations in North of Tunisia. (6th February 2014) - Ben Ammar, Imen; Harzallah-Skhiri, Fethia; Al Mohandes Dridi, Bouthaina
Abstract : In north of Tunisia, wild cardoon ( Cynara cardunculus L. var. sylvestris (Lamk) Fiori) is called "khurshef." It is consumed mainly for its fleshy stems and leafstalks in some traditional dishes. In some regions, heads were used to prepare cheese. North Tunisian germplasm has been currently damaged by severe genetic erosion, pollution, urbanization, and bad farming practices. In order to preserve this species and to assess morphological relationship between accessions, the present study aims to prospect and to characterize individuals in several areas of the north of Tunisia. Six populations were collected and then 20 individuals per population were evaluated using UPOV (International Union for the Protection of New Varieties of Plant) descriptors related to leaves, leafstalks, and heads. Multivariate analyses were used to elucidate relationship among the studied populations. Principal components analysis revealed more diversity within each population. Cluster study reveals large variability among populations. This analysis allows classifying the germplasm of wild cardoon into five groups. Similarities observed between ecotypes despite their distinctiveness of geographic origin suggest a narrow genetic base. These analyses are very useful for the management and the use of wild cardoon in future breeding programs for Cynara germplasm.